Body dissatisfaction and condom use self-efficacy: A meta-analysis. (January 2015) - Blashill, Aaron J.; Safren, Steven A.
Highlights: Body dissatisfaction and condom use self-efficacy were explored. Data were from 2495 participants across 11 studies. Meta-analytic results revealed r  = −.25, Cohen's d  = −0.52. As body dissatisfaction increases, condom use self-efficacy decreases. Abstract: The consistent use of condoms is the most effective behavior for reducing the acquisition of sexually transmitted infections (STIs), and condom use self-efficacy has been shown to be a key construct related to condom use. However, the examination of modifiable psychosocial and behavioral correlates of condom use self-efficacy is lacking. Recent investigations have highlighted the association of body dissatisfaction with condom use self-efficacy, and the current study conducted a meta-analysis on all available data addressing this relationship. Eleven individual effect-size parameters from nine studies yielded a total sample of 2495 men and women participants. A random-effects model revealed an average effect-size of r  = −.25, Cohen's d  = −0.52, which is moderate in strength. As body dissatisfaction increases, ones' self-efficacy regarding the use of condoms diminishes. Integrating interventions to decrease body dissatisfaction and sexual risk behaviors may prove to be an effective strategy to decrease STIs.